LIGHT REGULATION OF GROWTH AND MELANIN FORMATION IN Inonotus оbliquus (Pers.) Pilat - N. L. Poyedinok (Biotechnologia Acta, 2013)
The study aims to investigate possibilities of using different sources of low-intensity light for the regulation of mycelium growth and melanin synthesis by medicinal mushroom Inonotus obliquus (Pers.) Pilat.